(untitled) (Journal of Hama University, 2025)
This study aims to evaluate the effectiveness of the decision-making process in the management of physical preparation and sports in Syria. To achieve the study objectives, the descriptive approach was adopted by distributing a research questionnaire to an appropriate sample of leaders and workers in the management of physical preparation and sports in Syria, numbering (181) individuals, (157) questionnaires were retrieved, of which valid for analysis, with a recovery rate of (86.7%). In light of this, data was collected and analyzed and hypotheses tested using SPSS statistical package for social sciences. The study reached a number of results, the most important of which are: There is a high level of the decision-making process effectiveness in the management of Physical Preparation and Sports in Syria. The results also showed that there was a high evaluation score for all dimensions of the decision-making effectiveness in the organization under study, as the quality was the highest rated, followed by ease of implementation, then speed in decision-making... The study concluded with a set of recommendations, the most important of which is enhance the high level of the decision-making process effectiveness in the management of physical preparation and sports, and increase interest in the current administrative approach followed in making and taking decisions therein.